PREDICTORS OF CARDIAC ARREST IN CHILDREN - Stevanovic, Vesna; Bobos, Marin (Medical Research, 2026)
The incidence of cardiac arrest (CA) in pediatric patients is lower than in the adult population. The unique anatomical and physiological characteristics of children contribute to differences in the etiology of CA and the outcomes of resuscitation. Key factors for surviving a life-threatening event include the rapid recognition of CA and the prompt initiation of effective resuscitation. Therefore, identifying predictors of CA is crucial, as they indicate the potential for such an event and help differentiate affected patients from others. It is possible to prevent the occurrence of CA by appropriate treatment in these situations. Moreover, there are significant differences in the approach, implementation of resuscitation procedures, treatment, outcomes, and education regarding CA events that occur in children, whether they take place in-hospital or out-of-hospital.